Cardinal Stefan Wyszyński’s Concept of Christians Engagement in Culture - Ryszard Ficek (Warszawskie Studia Teologiczne)
The Christian concept of involvement in culture, as defined by Cardinal Stefan Wyszyński, exposes man in his entire personal vocation from the perspective of all essential dimensions of his existence. In this sense, all historical-political or socio-cultural processes - affecting society as a whole - always refer to a specific human person. In the context of all these essential dimensions, man is understood as a homo artifex. Thus, the fullness of man’s personal affluence becomes the ultimate and fundamental principle, subject, and goal of culture. Therefore, the article aims to answer the question: can the personalistic concept of a human being constitute the basis for forming and influencing the culture, especially in contemporary reality? Stefan Wyszyński’s personalism treats Christian involvement in culture regarding a vocation addressed to every human being. Moreover, by emphasizing elements such as the human person, family, nation, state, the international community, culture, economy, and politics, as well as the Church proclaiming the universal message of salvation, the personalistic vision of culture emphasizes its praxeological character, rooted in a specific human existence and oriented towards the supernatural dimension. Therefore, the human person is directly involved in the stream of modern civilization and its cultural changes, as well as finds his proper place in the dynamically changing realities of the contemporary world.